COVID-19 Infection Manifesting with Lumbar Spondylodiscitis Complicating With Psoas Abscess without Pneumonia - Erok, Berrin; Kıbıcı, Kenan (Indian Journal of Neurosurgery, 2021)
Extrapulmonary manifestations of COVID-19 (Coronavirus disease 2019) are increasingly recognized. Secondary spinal infections are dangerous complications reported in a few cases in the literature. However, to our knowledge, there is no reported case of a severe spondylodiscitis (SD) complicated with a large psoas abscess in a COVID-19 patient. We would like to report a 43-year-old male patient living in central Anatolia and dealing with farming who presented to the hospital with a complaint of severe back pain. The patient who was given oral treatment with analgesic, anti-inflammatory, and myorelaxant agents was readmitted with increased complaints. His nasopharyngeal swab was positive for COVID-19 without pneumonia on chest computed tomography (CT). He spent the quarantine and treatment period at home but was admitted to our outpatient clinic with a wheelchair with increased complaints and right leg pain preventing daily activities. The control nasopharyngeal swab was negative for COVID-19 but further increase in C-reactive protein (CRP) (152,8 mg/L) and creatine kinase (CK) level (549 IU/L) were revealed. Lumbar magnetic resonance imaging (MRI) showed SD in the L3-L4 level along with right-sided prevertebral inflammatory soft tissue and a large right psoas muscle abscess. Pyogenic lumbar SD complicated with the right psoas abscess in the setting of COVID-19 was considered and antibacterial treatment was started following hospitalization. On the same day, percutaneous aspiration from the psoas abscess under CT guidance was performed and revealed no growth in the culture. After 3 weeks, follow-up MRI showed worsening of all the bone, soft tissue and disc findings. Myalgia is a common manifestation in viral infections, which was also demonstrated in COVID-19 patients, with possible increase in muscle enzymes. Secondary spinal infections and its soft-tissue complications should be considered in the management of COVID-19 patients with neuromuscular symptoms, and detailed neurological and neurosurgical evaluation should be performed in order to avoid progression and permanent damage.
Keywords: Covid-19; Sars-CoV-2; spondylodiscitis; psoas abscess; endotheliitis